Studi Review Sistematis: Aplikasi Teori Disonansi Kognitif dan Upaya Reduksinya pada Perokok Remaja - Alexandra Tatgyana Suatan; Irwansyah Irwansyah (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Everyone agrees that smoking has a negative impact on health, including adolescents. The prevalence of adolescent smoking, which is still high, higher than the target of the Rencana Pembangunan Jangka Menengah Nasional (RPJMN), is a problem that has not been resolved from 2013 to the present. This problem solving difficulty is also driven by one of the elements of communication that occurs in adolescent smokers, namely cognitive dissonance. Cognitive dissonance is a feeling of discomfort experienced by a person when cognitive elements in him collide or are inconsistent. Adolescent smokers with cognitive dissonance are faced with the fact that smoking is harmful to health, but their behavior is inconsistent with this knowledge. The efforts made by teenagers to reduce discomfort are carried out in various ways. This study discusses two ways or concepts used by adolescent smokers to reduce cognitive dissonance that occurs using a systematic review method of previous literatures. The first concept is compensatory health belief (CHB) and self-exempting belief.